Fault transient response of generic Type 3 wind turbine models: Limitations and extension of the validation methodology. (October 2020) - Lorenzo-Bonache, A.; Honrubia-Escribano, A.; Fortmann, J.; Artigao, E.; Gómez-Lázaro, E.
Highlights: Generic wind turbine models for power system stability present certain limitations. This work compares IEC and WECC model responses focusing on the transient emulation. Field data from a real DFIG WT are used to validate the IEC and WECC generic models. An extension of the current validation methodology to transient periods is proposed. Abstract: Generic wind turbine (WT) models have amply demonstrated their capabilities for power system stability studies. These models, developed by the IEC and the WECC, can adapt their behavior to any actual WT with the adjustment of a limited number of parameters and reduced computational time. However, these generic models present certain limitations, especially during transient periods when a voltage dip begins and ends, the emulation of which is addressed differently by each guideline (IEC and WECC). The current validation methodology, proposed by the same IEC Standard that defines their models, dismisses transient periods for validation purposes, which involves a considerable information loss. In order to overcome this limitation, the current work studies in detail the consequences of the different modeling guidelines in transient emulation by comparing the response of the IEC and WECC models with field data obtained from a real Type 3 WT. To this end, six test cases performed with different voltage dips characteristics and loads on the real Type 3 WT are used. Furthermore, an extension of the current validation methodology to transient periods, which are currently neglected, is proposed in the present work.